“GenAI + blockchain” to coordinate agricultural supply chains to improve quality trust: an agent-based simulation study - Bai, Shizhen; Liu, Zijing; Wu, Wenya; Xu, Na; Jiang, Man (Frontiers in Sustainable Food Systems, 2025)
IntroductionIt is important to enhance consumer trust in the product quality of a sustainable agricultural supply chain. However, the frequent occurrence of food safety problems in practice leads to a lack of public confidence in food safety. To tackle the challenge of quality distrust, we harness the synergistic potential of “GenAI + blockchain” technology among industry-leading agribusinesses.MethodsThree distinct models are constructed to explore the impact of various technological integrations, with a focus on analyzing inventory management, operational efficiency, and precision technology adoption using AnyLogic.ResultsOur study reveals that (1) Integrating AI and blockchain technology can modulate minimum safety stock, catalyzing leapfrog revenue growth for enterprises. (2) Harnessing artificial intelligence can bolster the agricultural supply chain’s overall efficiency, but striving to achieve the highest possible accuracy is not feasible. (3) Gauging consumers’ premium for freshness aids companies in targeting key demographics and bolstering quality trust, thus fostering a stable upward trend in sales.DiscussionBy demystifying the underpinnings of minimum safety stock adjustments and the subtle effects of precision technology, our study steers the crafting of advanced inventory strategies and astute technology decisions for innovative agribusinesses.